As concepções de ensino-aprendizagem do Projeto Político-Pedagógico de uma escola de educação bilíngüe - David, Ana Maria Fernandes (2007)
This research aims to identify the teaching - learning approaches suggested by the political-pedagogical project of a bilingual school in the city of Sao Paulo. I have considered, in this investigation, that the educational work is also represented in texts institutionally produced, and so, I tried to identify in one of the documents produced by the school, the political-pedagogical project, aspects that characterise pedagogical actions such as the aims and objectives of education, the selection of academic knowledge, the role of mother tongue in the learning process of a second language, teacher s and student s roles, and the types of activities/homework that are part of the teaching-learning and evaluation process. To that matter, the following theoretical framework was used: the concept of political-pedagogical project (Vasconcellos, 1995/2004, Boutinet,1999/2002 and Padilha, 2006), the behaviourist teaching-learning theories (Skinner, 1974; Blomm, 1956/1973), the cognitivist theories (Piaget, 1956/1973; 1967/2003;1970/2002), the socio-historical-cultural theories (Vygotsky, 1984:2003; 1987/2000; 2001;2004) and the meanings of bilingual education (Hutchison & Waters, 1987,1992;Hamers & Blanc, 1989; Baker, 2000, 2001; Lantolf, 2000). The option to carry out the research within the field of applied linguistics was made for two reasons. First, due to the possibility of developing a critical reflection using the language that constitutes the pedagogical practice. Also, to consider the document produced by the school as a text that carries guidelines for the educational work (Amigues, 2004; Nourodine, 2002). The data were collected in a bilingual school in the city of Sao Paulo which develops this proposal in the primary and secondary school; the data selection included only the data from the secondary school. The data analysis was based on the procedures proposed by Bronckart (1997/1999) and Bronckart & Machado (2004). It aimed at identifying in the analysed text the teaching-learning approaches of the plan of contexts, the plan of the discourse, the plan of textual organisation, specifically in relation to the thematic content and the lexical choices. The results of the analysis led me to believe that different teaching-learning approaches constitute the political-pedagogical project, and this diversity should be part of the academic day-by-day practice